Implementation of Immersive Customer Experience Strategy by Customer Care XYZ to Improve Consumer Satisfaction and Loyalty - Nursiwan Dinata Candra; Alldila Nadhira Ayu Setyaning (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the implementation of the Immersive Customer Experience (ICE) strategy by Customer Care XYZ at XYZ in enhancing customer satisfaction and loyalty. The ICE strategy combines physical and digital experiences in a personalized manner to create emotional connections between customers and the brand. This research employs a qualitative approach using a case study method. Data were collected through field observations, in-depth interviews with three key informants, and documentation. The findings reveal that it has implemented various programs such as Mudik Bersama, Posko Mudik, the MX application, after-sales services, and birthday greetings, which reflect the ICE strategy, although not explicitly labeled as such. These programs have proven effective in creating positive and immersive customer experiences, thereby improving customer satisfaction and loyalty toward XYZ. This study also offers recommendations for optimizing experience-based marketing strategies to strengthen long-term customer relationships.